Integration of Islamic Character Values in the Implementation of the Independent Curriculum in Fiqh Learning - Firman; M Sayyidul Abrori; Rina Mida Hayati (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to describe and analyze the integration of Islamic character values ​​in the implementation of the Merdeka Curriculum in Islamic jurisprudence (Fiqh) learning at MA Bumi Sholawat Wates. This research is motivated by the importance of character education in developing students who are not only cognitively superior but also possess good morals, as well as the gap between curriculum objectives and field practice. The approach used was qualitative with a descriptive approach. The research subjects included Islamic jurisprudence teachers, madrasah principals, and students selected through purposive sampling. Data collection was conducted through observation, interviews, and documentation, while data analysis employed an interactive model encompassing data reduction, data presentation, and conclusion drawing.The results indicate that the integration of Islamic character values, namely discipline, responsibility, honesty, and social awareness, has been systematically implemented through the practice of worship, assignments, teacher role models, and collaborative learning activities. Teachers' strategies include linking Islamic jurisprudence (fiqh) material to real life, fostering positive behavior, and providing consistent role models, ensuring that character values ​​are not only cognitively understood but also internalized in students' behavior. Therefore, Islamic jurisprudence (fiqh) learning in the implementation of the Independent Curriculum plays a strategic role as a medium for internalizing Islamic character values, capable of developing students with noble character and supporting the realization of the Pancasila Student Profile.